Determining the viscoelastic properties obtained by depth sensing microindentation of epoxy and polyester thermosets using a new phenomenological method. (2nd January 2015) - Kohl, James G; Schwarzer, Norbert; Ngo, Truc T; Favaro, Gregory; Rengnet, Eric; Bierwisch, Nick
Abstract: Epoxy and polyester thermosets are currently used as the polymer matrix material for many fiber-reinforced composite systems. The viscoelastic properties of these materials were investigated in this study by use of depth sensing microindentation. The microindentation tests performed had the load being applied at a rapid loading rate to a maximum load. This maximum load was held constant while the stylus continued to sink. It was then unloaded at a nominal rate. A new phenomenological model developed by Schwarzer in 2014 was used in this work to determine the viscoelastic properties. Two approaches or methods were used. The first method involved determining the three parameters by using hold time data combined with unloading data (this method is referred to in this work as 'hold time method'). The second method used only the unloading data (this method is referred to in this work as 'unloading method'). It was shown that the properties determined by the two methods are not the same but are dependent upon the strain rate behavior during the indentation test. Low load scratch tests were also performed. It was seen that as the sliding speed increased the depth of penetration decreased resulting in the coefficient of friction also decreasing. An understanding of the viscoelastic properties at the surface and how they affect friction are important in studying wear of these materials.